Variability in Stiffness Assessment in a Thyroid Nodule Using Shear Wave Imaging. Issue 4 (December 2015) - Brezak, Robert; Hippe, Dan; Thiel, Jeff; Dighe, Manjiri K.
Abstract : Purpose: The aim of the study was to assess intrareader and interreader variability in placing a region of interest in the elastography color map in the thyroid nodule. Method and Materials: After institutional review board approval, elastograms were obtained by shear wave elastography from 38 individuals, with a total of 60 thyroid nodules. Two readers reviewed all images while blinded to the cytopathology or final histopathology results and to each other's measurements. For each image, readers first performed a qualitative assessment and recorded presence of stiff region(s) and number of stiff regions. Then, they placed a 3-mm circular region of interest on the stiffest region to quantify the mean and maximum stiffness in kilopascals. Intrareader and interreader agreement was summarized for categorical variables using Cohen κ and for continuous variables using the concordance correlation coefficient (CCC) and coefficient of variation. Results: There was good overall intrareader and interreader agreement for the presence of stiff regions and number of stiff regions after classifying them as 0, 1, and greater than 1 regions (κ = 0.78–0.81 and 0.74–0.79, respectively). There was also good overall agreement for the the following quantitative measurements: mean kPa (CCC = 0.97 and 0.93) and max kPa (CCC = 0.97 and 0.93). The intrareader and interreader coefficient of variation was 13% and 21% for mean kPa and 14% and 21% for max kPa. Conclusions: There can be differences in measurement of stiffness by 2 different operators in softer nodules with shear wave imaging because of the lack of brighter areas on the color elastograms. A standardized technique is necessary to be able to compare results from 1 study to the next.